2002
DOI: 10.1182/blood.v99.2.437
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden: a genetic risk factor for thrombotic microangiopathy in patients with normal von Willebrand factor–cleaving protease activity

Abstract: Thrombotic microangiopathy (TM) is associated with abnormalities of von Willebrand factor-cleaving protease (VWCP) and other hemostatic factors. This study hypothesized that TM patients might have genetically determined thrombotic risk factors that predispose them to aberrant microvascular thrombosis. DNA samples from 30 white and 12 African American adult TM patients were analyzed for genetic alleles associated with vascular thrombosis, and plasma samples were analyzed for levels of VWCP activity. DNA was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 50 publications
2
45
0
1
Order By: Relevance
“…The cleavage of multimeric VWF by leukocyte proteases was analyzed in a modified version of the assay described by Furlan et al 21 and Raife et al 22 Purified VWF (Humate P; ZLB Behring GmbH) at a final concentration of 3 U/mL was incubated with enzymes for various times at 37°C in 5 mM Tris buffer, pH 8.0, with or without 1.5 mM urea. Final enzyme concentrations in the reaction were as follows: elastase 138 nM, PR3 172 nM, and cathepsin G 8.6 nM.…”
Section: Cleavage Of Multimeric Vwf Under Denaturing Conditionsmentioning
confidence: 99%
“…The cleavage of multimeric VWF by leukocyte proteases was analyzed in a modified version of the assay described by Furlan et al 21 and Raife et al 22 Purified VWF (Humate P; ZLB Behring GmbH) at a final concentration of 3 U/mL was incubated with enzymes for various times at 37°C in 5 mM Tris buffer, pH 8.0, with or without 1.5 mM urea. Final enzyme concentrations in the reaction were as follows: elastase 138 nM, PR3 172 nM, and cathepsin G 8.6 nM.…”
Section: Cleavage Of Multimeric Vwf Under Denaturing Conditionsmentioning
confidence: 99%
“…7,42 Similar to our observations, an additional study reported that 12 (29%) of 42 patients with TTP-HUS were African American; 11 (37%) of 30 patients who had ADAMTS13 deficiency were African Americans, and only 1 (8%) of 12 patients who did not have ADAMTS13 deficiency was African American. 24 The explanation for the increased relative frequency of African Americans among patients with clinically diagnosed TTP-HUS is unknown.…”
mentioning
confidence: 99%
“…5,11 Briefly, 98 lL of undiluted sample plasma mixed with 50 lL of purified VWF (final concentration 3U/mL), 10 mmol/L Pefabloc SC (Boehringer, Mannheim, Germany), and 8 lL of 10 mmol/L BaCl 2 , was dialyzed (1.5 mol/L urea, 0.005 mol/L Tris, pH 8.0) in a hydrophilic filter membrane (VSWP, 47-mm diameter; Milipore, Bedford, MA) for 15 hours at 378C. The reaction was quenched with 10 lL of 0.2 mol/L EDTA, pH 7.4.…”
Section: Adamts13 Assaymentioning
confidence: 98%
“…5,11,12 In this study, TMA refers to disorders usually referred to by referring physicians as TTP, HUS, or TTP/HUS, which, by the standards of care in southeastern Wisconsin, warranted treatment by plasma exchange. The diagnostic criteria for TMA in this study included thrombocytopenia, microangiopathic hemolytic anemia, elevated lactate dehydrogenase, and absence of a diagnosis of disseminated intravascular coagulation or other plausible alternative diagnosis.…”
Section: Patients and Samplesmentioning
confidence: 99%